Molecular cloning and sequence variations of cDNA encoding for trypsin inhibitor from kelampayan (Neolamarckia cadamba) - Melanie Ann, Perera (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Proteinase inhibitors are important in plant defense mechanisms. The gene that is responsible for it is Kunitz-type trypsin inhibitor (KTI) which reduces the digestability and nutritional quality of the leaves of the tree which is infected by insect pests or microbes. The objectives of this study are to clone the cDNA encoding for trypsin inhibitor and to identify single nucleotide polymorphisms (SNPs) through in-silico analyses. Neolamarckia cadamba (Kelampayan) is used in this study because of its fast growth rate and economic importance. Total RNA was isolated from developing xylem samples and reverse transcribed into cDNA. The ~323 bp gene was then amplified and cloned into pGEM-ⓇT Easy vector systems and sent for automated sequencing. Results showed that a miraculin-like gene was isolated. Further analysis revealed that the gene belongs to the plant Kunitz serine trypsin inhibitor (STI) family of proteinase inhibitors, with the same functions as KTI gene. A total of 27 SNPs were identified with 22 synonymous and 5 non-synonymous.